Experimental Study Of Plates With Polymer Coatings For Resistance Under Compression - et. al., A.G. Getmanov, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Polymer coatings are widely used in various fields of technology to protect structural elements from corrosion, to provide electrical insulation, to control the frictional characteristics of surfaces, for decorative purposes, etc. [1]. Reliable identification of the mechanical properties of coatings is an important task from the point of view of ensuring their strength and wear resistance during operation process [1-8]. Here, the mechanical properties of epoxy-polyester-based coatings used for corrosion protection of structural elements of aviation equipment are determined. On the basis of a sequence of experimental studies and theoretical calculations, the elastic modulus of the coating material, the residual stresses acting in it arising from the use of heat treatment in the process of coating deposition [9-13] and the adhesion strength of the coating to the substrate under conditions of complexly stressed heating are determined. The results obtained can be used both to assess the strength and durability of the coating material, and to assess their influence on the mechanical behavior of protected thin-walled structures.